SUPERVISION OF THE FORMATION OF LOCAL REGULATIONS BY THE GOVERNOR IN THE INDONESIAN REGIONAL AUTONOMY PERSPECTIVE - Fikri Hadi; Sukardi; Farina Gandryani (DE RECHT (Journal of Police and Law Enforcement), 2024)
Constitutional Court Decision Number 137/PUU-XIII/2015 and Constitutional Court Decision No. 56/PUU-XIV/2016 changed the supervision mechanism of local regulations in Indonesia. The verdict revoked the authority of the Minister of Home Affairs and the Governor. This is a legal research with conceptual and statute approach. The governor still has the authority to cancel local regulations, as determined from the results of the discussion. The governor can conduct preventive supervision and executive preview when the local regulation is still in the form of a draft. Executive preview can take the form of facilitation by the governor and/or harmonization of district/city regional regulations through the legal bureau in the province.